Reciprocal interferences of the left ventricular assist device and the aortic valve competence - Vriz, Olga; Mushtaq, Ali; Shaik, Abdullah; El-Shaer, Ahmed; Feras, Khalid; Eltayeb, Abdalla; Alsergnai, Hani; Kholaif, Naji; Al Hussein, Mosaad; Albert-Brotons, Dimpna; Simon, Andre Rudiger; Tsai, Felix Wang (Frontiers in Cardiovascular Medicine, 2023)
Patients suffering from end-stage heart failure tend to have high mortality rates. With growing numbers of patients progressing into severe heart failure, the shortage of available donors is a growing concern, with less than 10% of patients undergoing cardiac transplantation. Fortunately, the use of left ventricular assist devices (LVADs), a variant of mechanical circulatory support has been on the rise in recent years. The expansion of LVADs has led them to be incorporated into a variety of clinical settings, based on the goals of therapy for patients ailing from heart failure. However, with an increase in the use of LVADs, there are a host of complications that arise with it. One such complication is the development and progression of aortic regurgitation (AR) which is noted to adversely influence patient outcomes and compromise pump benefits leading to increased morbidity and mortality. The underlying mechanisms are likely multifactorial and involve the aortic root-aortic valve (AV) complex, as well as the LVAD device, patient, and other factors, all of them alter the physiological mechanics of the heart resulting in AV dysfunction. Thus, it is imperative to screen patients before LVAD implantation for AR, as moderate or greater AR requires a concurrent intervention at the time of LVADs implantation. No current strict guidelines were identified in the literature search on how to actively manage and limit the development and/or progression of AR, due to the limited information. However, some recommendations include medical management by targeting fluid overload and arterial blood pressure, along with adjusting the settings of the LVADs device itself. Surgical interventions are to be considered depending on patient factors, goals of care, and the underlying pathology. These interventions include the closure of the AV, replacement of the valve, and percutaneous approach via percutaneous occluding device or transcatheter aortic valve implantation. This paper aims to assess the prevalence of de-novo AR or the progression of AR after LVAD implantation, its implications on the prognosis, and discuss the possible management options. We also provide a comprehensive echocardiographic strategy for the precise assessment of AV dysfunction.